Interannual to Centennial-Scale Changes in Southeast Asian Hydroclimate during the Common Era - Wang, Jessica (eScholarship, University of California, 2020)
The Asian Monsoon system impacts more than two-thirds of the world’s population each year by supplying the necessary water resources to sustain agriculture, the economy, and the socioeconomic welfare for billions of people. In recent decades, changes in the strength and spatial extent of the monsoon have led to significant drought and flooding events. Currently, climate models do not agree on future changes in monsoonal rainfall. In order to improve projections of changes in the Asian Monsoon, it is important to investigate how the monsoon has varied in the past. Climate proxy records obtained through archives (such as cave deposits) provide evidence for changes in past climate on a range of timescales. My dissertation focuses on the Southeast Asian region, where few paleoclimate records that span the last 2,000 years currently exist. I present the first, high-resolution speleothem record from northern Laos. The carbon stable isotope (δ13C) record reveals decades-long megadroughts, consistent with previous findings from regional tree ring records, whereas the oxygen stable isotope (δ18O) record, interpreted as changes in monsoon intensity, exhibits a relationship with solar variability. I identify that multidecadal to centennial-scale shifts in monsoon intensity are linked with solar-forced changes in tropical Atlantic sea surface temperatures. I also examine the modern interannual variability of precipitation across East China and Southeast Asia over the last 30 years. I show that spatial tripole and dipole rainfall patterns are linked with the El Niño Southern Oscillation and North Atlantic Oscillation, respectfully. Finally, I evaluate how different water pathways and in-cave properties may influence speleothem δ18O values at our cave site using an integrated speleothem forward model and cave monitoring data. I conclude that combined effects of karst hydrology and in-cave processes contribute to speleothem δ18O variability. The collective results of my dissertation help us better understand changes in Southeast Asian hydroclimate on a variety of spatial and time scales. This research builds upon the limited number of paleoclimate records from Laos and the surrounding countries, while contributing to modern rainfall analyses and proxy system modeling studies to better interpret paleoclimate records and improve projections of monsoon rainfall.